Jahe Peningkat Sistem Imun Tubuh di Era Pandemi Covid- 19 di Kelurahan Kadia Kota Kendari: Ginger Improves the Body's Immune System During a Pandemic Covid-19 in a Village in Kendara City - Ratna umi nurlila; Jumarddin La Fua (Progran Studi Farmasi STIKES Mandala Waluya, 2020)
Covid-19 is a new disease that has become a pandemic, this disease must be watched out for because the transmission is relatively fast, has a mortality rate that cannot be ignored. Until now, cases of Covid 19 virus sufferers have continued to increase, cases in landmark Sulawesi reached 3,568 positive confirmed cases, 2,348 recovered cases and 66 cases died. (Media Indonesia in covid 19, 2020). It is suspected that this case will continue to increase if public awareness of complying with health protocols is not implemented. Besides that, it is necessary to increase the body's immune system considering that the virus can enter the human body when the immune system is decreased. The body's immune system is important to maintain in the current Covid 19 era, one of the natural resources that is quite abundant in Southeast Sulawesi at a low price and has a high enough antioxidant content is ginger rhizome, this ginger rhizome is often found in traditional markets and farmers. In addition, ginger rhizome contains a lot of active compounds that are healthy for the body, in the midst of limited supply of vitamin C production and it is difficult to reach for the middle to lower class, this ginger rhizome really helps people in increasing the immune system. This community service activity is carried out in Kadia sub-district, Kadia sub-district, Kendari city, considering that from June to October there has been an increase in the number of positive cases of Covid in this area, it is very necessary to provide education to the community and invite the community, especially in this place of service, to continue to obey healthy protocol and maintaining the body's immune system by consuming ginger with several preparations, as well as planting ginger in the yard of the house as a means of providing ginger for the family.